2017
DOI: 10.1002/bem.22026
|View full text |Cite
|
Sign up to set email alerts
|

Study of potential health effects of electromagnetic fields of telephony and Wi‐Fi, using chicken embryo development as animal model

Abstract: The objective of this study is to investigate possible biological effects of radiofrequency electromagnetic fields (RF-EMF) as used in modern wireless telecommunication in a well-controlled experimental environment using chicken embryo development as animal model. Chicken eggs were incubated under continuous experimental exposure to GSM (1.8 GHz), DECT (1.88 GHz), UMTS (2.1 GHz), and WLAN (5.6 GHz) radiation, with the appropriate modulation protocol, using a homogeneous field distribution at a field strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Electromagnetic stimulation providing various parameters during incubation has no effect on chicken morphology. There is no effect on tissue or gene expression ( Woelders et al, 2017 ). However, another study showed that microwave frequency electromagnetic fields produced stress on embryonic cells and increased Hsp70 protein levels without causing a significant temperature increase ( Shallom et al, 2002 ).…”
Section: Physiological Processes Of Muscle Fiber Developmentmentioning
confidence: 99%
“…Electromagnetic stimulation providing various parameters during incubation has no effect on chicken morphology. There is no effect on tissue or gene expression ( Woelders et al, 2017 ). However, another study showed that microwave frequency electromagnetic fields produced stress on embryonic cells and increased Hsp70 protein levels without causing a significant temperature increase ( Shallom et al, 2002 ).…”
Section: Physiological Processes Of Muscle Fiber Developmentmentioning
confidence: 99%
“…Several studies have investigated the potential health effects of exposure to microwave radiation, EMFs, Radiofrequency (RF), and radiofrequency electromagnetic radiation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Individuals living within <300 meters of mobile base stations reported more frequent symptoms of nausea, headache, dizziness, irritability, discomfort, nervousness, depression, sleep disturbance, memory loss, and diminished libido compared to those living further away (>300 meters) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the human body endures continuous electromagnetic (EM) exposure stemming from mobile communication infrastructures, especially from base station towers [3]. The proliferation of wireless network technologies, including wireless local area network (WLAN) hotspots and Wi-Fi networks, also escalates the potential for excessive radiation exposure in the radiofrequency EM spectrum [4]. Research has disclosed elevated EM radiation levels in urban areas across different countries [5].…”
Section: Introductionmentioning
confidence: 99%